Students’ Assessment of Learning in a Volleyball Course at a University: A Mixed Methods Study - Ivar Fossland Moa; Pål Lagestad; Arne Sørensen (Education Sciences, 2024)
The aim of the study was to evaluate students’ assessment of their learning after a teaching period of volleyball training in a university course. The teaching was research-based and linked to relevant theories of motor learning, small-sided games (SSG), teaching games for understanding (TGfU), and motivational climate. To examine the research question, a mixed methods design was used, which included a questionnaire and reflection notes from the students. The questionnaire data constituted the basis for an analysis of the students’ reported development in their skills and knowledge in four relevant learning outcomes, while the qualitative data provided more in-depth data related to their learning. The statistical analyses showed a significant increase in the experience of skills and knowledge in all four relevant learning outcomes related to the curriculum of the course. From reporting poor or medium goal achievement prior to the course, the students, in general, reported good goal achievement after the course. The thematic analysis of the reflection notes supported these findings, in which game activities in small groups were especially identified as positive. Furthermore, the students stated that the teacher and a learning-oriented motivational climate were crucial in contributing to a positive learning environment. Some of the students reported too little instruction and feedback from the teacher during the course. The students expressed a few suggestions for changes to the content and methodology of the teaching. The study indicates that this type of research-based teaching may be important to produce a positive learning outcome for students. Our finding is consistent with previous research, which identifies which elements should be emphasized when implementing training in this subject area. As the survey only had 30 respondents and the design did not contain a control group, caution should be exercised when drawing strong conclusions from this study.